Exploring International Legal Challenges For Unhcr In Dealing With Rohingya Refugees In Aceh, Indonesia - Hasanah, Uswatun; Binti Ibrahim, Elly Adriana (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2024)
The difficulties the UNHCR has managing Rohingya refugees in Indonesia are the main topic of this article. This article focuses on the challenges faced by the United Nations High Commissioner for Refugees (UNHCR) in managing Rohingya refugees in Indonesia. As the primary international agency tasked with refugee management globally, the UNHCR plays a crucial role in preventing statelessness, determining refugee status, and providing comprehensive remedies. However, the study reveals that despite receiving approval from the Indonesian government to operate, the UNHCR encounters difficulties in fulfilling its mandate to assist Indonesia's ethnic Rohingya refugees. This limitation is attributed to the escalating number of asylum seekers in Indonesia requiring aid. The research utilizes content analysis to delve into UNHCR's struggles with Rohingya refugees, gathering and analyzing various sources such as reports, studies, news, and policies related to Rohingya refugees in Aceh. Through this method, the study uncovers patterns and challenges encountered by the UNHCR, including managing crises and navigating international and local cooperation. Ultimately, this research provides a detailed understanding of the complexities surrounding the Rohingya refugee crisis in Aceh.